Whole-genome survey reveals interspecific differences in genomic characteristics and evolution of Pampus fish - Zhao, Xiang; Zheng, Tianlun; Song, Na; Qu, Yinquan; Gao, Tianxiang (Frontiers in Marine Science, 2024)
Pampus belongs belong to the Perciformes, Stromateoidei, Stromateidae, and are widely distributed throughout the Indian Ocean and the Western Pacific. In this study, we employed next-generation sequencing to generate comprehensive genomic data for Pampus punctatissimus and Pampus echinogaster, and subsequently compared the obtained genomic information with the published data of Pampus argenteusHere, next-generation sequencing was used to generate genome-wide data to provide genomic information of Pampus punctatissimus and Pampus echinogaster, and the published genomic data of Pampus argenteus was compared with them. P. echinogaster wasidentified to be the largest genome size (602 Mb), heterozygosity (1.38%) and repetitive sequence ratio (33.06%), while similar genome sizes between P. punctatissimus (540Mb) and P. argenteus (550Mb) were observed. A total of 402,921 and 628,298 SSRs were identified for P. punctatissimus and P. echinogaster, respectively.Additionally,In addition. 1876, 638 and 394 single-copy homologous genes were identified from P. punctatissimus, P. echinogaster and P. argenteus respectively. The KEGG enrichment results of the unique single-copy genes to the three species were significantly different in genetic information processing, protein processing and metabolic functions. The complete mitochondrial genomes of P. punctatissimus and P. echinogaster were successfully assembled, and the resulting phylogenetic relationships align with the currently reported taxonomic status of species in the Stromateoide.Additionally, population size analysis using PSMC revealed that P. punctatissimus experienced one bottleneck effect, while P. echinogaster underwent two bottleneck events during the Pleistocene Glacial EpochComplete mitochondrial genomes of P. punctatissimus and P. echinogaster were assembled and the phylogenetic relationships were consistent with the currently reported taxonomic status of species in the Stromateoidei. PSMC analysis showed that P. punctatissimus and P. echinogaster experienced one and two bottleneck effects during the Pleistocene Glacial Epoch, respectively.